Scanning electron microscopic and profilometric study of different sharpening stones - Andrade Acevedo, Roberto Antonio; Cardozo, Ana Karina Veloso; Sampaio, José Eduardo César [UNESP] (FapUNIFESP (SciELO), 2006)
Scaling and root planing contribute to the recovery of periodontal health. All periodontal instruments loose their fine cutting angle after use. To maintain this angle, correct sharpening is required using specifically designed stones. The characteristics of sharpening stones can be compared to the blade of the instruments and also transported to root surface during instrumentation. Root smoothness is related to the quality of the blade. Therefore, the purpose of this study was to evaluate the characteristics of 9 sharpening stones by scanning electron microscopic and profilometric analyses. Ceramic and Neumar stones were very fine and both may be recommended to maintain the sharpness of the instruments. Arkansas, Thompson and CE stones presented greater roughness with very regular and round particles, and are suitable for maintenance of the cutting angle. In addition, these stones may be indicated for the routine sharpening of the instruments that are partly dull. Oxide Aluminum, Carborundum and JON stones were the coarsest with large irregular particles and may be indicated for initial sharpening of totally dull instruments with completion of sharpening with finer stones.
Keywords: Dental instruments; Roughness; Scaling; Scanning electron microscopy; Sharpening stones; aluminum oxide; inorganic compound; ceramics; chemistry; dental equipment; equipment design; human; particle size; scanning electron microscopy; surface property; Aluminum Oxide; Carbon Compounds, Inorganic; Ceramics; Dental Instruments; Equipment Design; Humans; Microscopy, Electron, Scanning; Particle Size; Surface Properties